2013
DOI: 10.1016/j.jval.2013.03.546
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact of pregabalin for the treatment of neuropathic pain in Colombia

Abstract: Acupuncture use was nearly six times more common among chiropractic users than in the overall population (2.2% vs. 0.37%); similarly, nearly half (42.5%) of acupuncture users also had a claim for chiropractic. Over one-in-five patients (21.0%) with general joint or back pain used chiropractic, of which 2.65% also used acupuncture. CONCLUSIONS: Despite trends suggesting increased use of chiropractic and acupuncture, their use remains very low in commercial health insurance plans, including patients with inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The 23 studies reported data for Brazil (n = 7), 53–58 – 65 Argentina (n = 5), 47 , 48 - 50–52 , Colombia (n = 4), 59–61 64 Mexico (n = 3), 63 , 66 , 68 Costa Rica (n = 1), 62 Nicaragua (n = 1), 69 and Latin America [including Brazil, Mexico and Argentina] (n = 1) 49 whereas one multi-regional study provided aggregate results for Latin America (n = 1), 67 with the same countries included ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 23 studies reported data for Brazil (n = 7), 53–58 – 65 Argentina (n = 5), 47 , 48 - 50–52 , Colombia (n = 4), 59–61 64 Mexico (n = 3), 63 , 66 , 68 Costa Rica (n = 1), 62 Nicaragua (n = 1), 69 and Latin America [including Brazil, Mexico and Argentina] (n = 1) 49 whereas one multi-regional study provided aggregate results for Latin America (n = 1), 67 with the same countries included ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides an overview of cost per patient data. Studies reported different perspectives when estimating costs such as social perspective (n = 3), 49 , 59 , 60 third-party payer perspective (n = 1) 64 and the public perspective (n = 1). 65 Out-of-pocket expenses were reported in two studies.…”
Section: Resultsmentioning
confidence: 99%